PENGARUH BUDAYA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PADA PEGAWAI KANTOR GUBERNUR PROVINSI KALIMANTAN TIMUR - Puteri, Annisa; Anitra, Vera; Hadiyanti, Sofia Ulfa Eka (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2025)
This study aims to analyze the effect of work culture and work motivation on employee performance at the Leadership Administration Bureau of the East Kalimantan Provincial Governor’s Office. The entire population of 69 employees was included as the research sample using a total sampling technique. This research employed a quantitative approach with a survey method, utilizing questionnaires as the primary data collection instrument. Data analysis was conducted using multiple linear regression. The results indicate that work culture and work motivation have a positive and significant effect on employee performance, both partially and simultaneously. Work culture was found to have a more dominant influence compared to work motivation. These findings highlight the importance of creating a conducive work environment and providing appropriate motivation to enhance employee productivity and performance effectiveness within government bureaucracy.